High-strain-rate mechanical response and anisotropic behavior of magnesium alloys with varying zinc content - Tianshuai Yang; Yunfei Hou; Weiying Huang; Zhihao Deng; Haifeng Liu; Ziang Yang; Kaipeng Tian; Taku Sakai; Ming-Chun Zhao (Journal of Materials Research and Technology)
This work investigated the effect of Zn content on the mechanical behavior and deformation mechanism of Mg–Mn–Zn alloys during high-speed impact along the extrusion direction (ED) and transverse direction (TD). The sample designations were: ZM04 (0.4 wt% Zn), ZM06 (0.6 wt% Zn), ZM08 (0.8 wt% Zn), ZM10 (1.0 wt% Zn), ZM15 (1.5 wt% Zn). The results showed that, under both quasi-static and high-speed impact loading, the compressive strength of the ED samples was significantly higher than that of the TD samples, while the compressive strain was lower in the ED samples. The primary high-speed impact deformation mechanism in the ED samples included {10 1‾ 2} tensile twinning, basal slip, and pyramidal <c + a> slip; while in the TD samples, the main mechanism involved basal slip, accompanied by {10 1‾ 1} compressive twinning and pyramidal <c + a> slip. In addition, kink-induced deformation mechanism was observed in both ED and TD samples, facilitating deformation under high strain rates. The ZM08-ED samples had the best overall performance due to the synergistic effects of grain refinement, texture strengthening, Zn precipitation strengthening, and solid solution strengthening. This work provides valuable theoretical insights for the development of high-performance Mg–Mn–Zn alloys in high-speed impact applications.